Chromatin state changes during neural development revealed by in vivo cell-type specific profiling - Owen J. Marshall (Nature Portfolio, 2017)
While transitions between active and repressive chromatin states are essential for differentiation, little is known regarding their role during development of the brain in Drosophila. Here, the authors investigate the large scale chromatin remodelling taking place during fly neural development.